2011
DOI: 10.1074/jbc.m110.186049
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis and Involvement in Plant Innate Immunity of Xanthomonas axonopodis pv. citri Lipopolysaccharide

Abstract: Xanthomonas axonopodis pv. citri (Xac) causes citrus canker, provoking defoliation and premature fruit drop with concomitant economical damage. In plant pathogenic bacteria, lipopolysaccharides are important virulence factors, and they are being increasingly recognized as major pathogen-associated molecular patterns for plants. In general, three domains are recognized in a lipopolysaccharide: the hydrophobic lipid A, the hydrophilic O-antigen polysaccharide, and the core oligosaccharide, connecting lipid A and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 60 publications
(57 reference statements)
6
65
2
1
Order By: Relevance
“…Positive selection for evolution of Xac Y Zhang et al genes in this region, such as wxacO, rfbC, nlxA and wzt, have been demonstrated to be involved in O-antigen synthesis and transport and be associated with biofilm formation on the host and contribute to virulence in XacA (Casabuono et al, 2011;Li and Wang, 2011;Petrocelli et al, 2012;Yan et al, 2012). Among the three components, lipid A, core and O-antigen that are composed of the entire Xac LPS, the O-antigen region is probably the most important for host basal response during citrus-pathogen interaction (Casabuono et al, 2011).…”
Section: Genomic Features Of Citrus Canker-causing Xac Strainsmentioning
confidence: 99%
“…Positive selection for evolution of Xac Y Zhang et al genes in this region, such as wxacO, rfbC, nlxA and wzt, have been demonstrated to be involved in O-antigen synthesis and transport and be associated with biofilm formation on the host and contribute to virulence in XacA (Casabuono et al, 2011;Li and Wang, 2011;Petrocelli et al, 2012;Yan et al, 2012). Among the three components, lipid A, core and O-antigen that are composed of the entire Xac LPS, the O-antigen region is probably the most important for host basal response during citrus-pathogen interaction (Casabuono et al, 2011).…”
Section: Genomic Features Of Citrus Canker-causing Xac Strainsmentioning
confidence: 99%
“…Plants recognize certain LPSs as microbe-associated molecular patterns (MAMPs), which trigger innate defense responses (14)(15)(16)(17). In Arabidopsis, both the core and lipid A of Xanthomonas campestris LPS trigger independently the induction of the defense genes PR1 and PR2 (15).…”
mentioning
confidence: 99%
“…citri lacking the O chain than by the wild type, suggesting a defense-eliciting role for the O chain as well; notably, this O chain has a structure somewhat distinct from that of X. campestris pv. campestris (17).…”
mentioning
confidence: 99%
“…Xcc causes citrus canker disease, and has previously been chosen as a model for investigating the molecular determinants of host specialization (Brunings and Gabriel, 2003). Xcc contains typical pathogen-associated molecular patterns (Casabuono et al, 2011) and 25 type three secretion system effectors (da Silva et al, 2002). It is well documented that Meiwa kumquat (Fortunella crassifolia) is immune to Xcc and shows a hypersensitive response (HR) reaction to Xcc infection (Khalaf et al, 2008;Fu et al, 2012), whereas grapefruit (Citrus paradise) is one of the highly susceptible citrus varieties (Gottwald and Graham, 2000).…”
mentioning
confidence: 99%